Nutrient intake and food habits of soccer players: Analyzing the correlates of eating practice - Garcia-Rovés, P, M.; Garcia-Zapico, P.; Ángeles M.; Patterson, A. M.; Iglesias-Gutiérrez, E. (Nutrients, 2014)
Despite the impact and popularity of soccer, and the growing field of soccer-related scientific research, little attention has been devoted to the nutritional intake and eating habits of soccer players. Moreover, the few studies that have addressed this issue suggest that the nutritional intake of soccer players is inadequate, underscoring the need for better adherence to nutritional recommendations and the development and implementation of nutrition education programs. The objective of these programs would be to promote healthy eating habits for male and female soccer players of all ages to optimize performance and provide health benefits that last beyond the end of a player`s career. To date, no well-designed nutrition education program has been implemented for soccer players. The design and implementation of such an intervention requires a priori knowledge of nutritional intake and other correlates of food selection, such as food preferences and the influence of field position on nutrient intake, as well as detailed analysis of nutritional intake on match days, on which little data is available. Our aim is to provide an up-to-date overview of the nutritional intake, eating habits, and correlates of eating practice of soccer players.